(untitled) - Ulrich, Katherine (Berkeley, C.A., 2001)
This book introduce the Flash editor, creating simple graphics. Modifying simple graphics. Animation with motion tweening. Animation with shape tweening, more-complex animation tasks...
Keywords: Flash (tệp máy tính),Flash (Computer file)